ON SIMPLE MONADIC PROLOG INTERPRETER - Hambardzumyan, A. M. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2001)
In this paper we discuss questions concerning transformations of PROLOG-programs and PROLOG-queries intended for extension of intellectual abilities of the interpreter. Some subset of simple monadic PROLOG is considered. It is proved that one cannot transform any program and query from this subset in such a way that the interpreter will always stop with a definite answer, but it is possible to do it if the query is a logical consequence of the program.